Continuity and change in the garbage village of Muqattam - Mohamed, Bassant (AUC Knowledge Fountain, 2019)
This dissertation provides an agency-oriented approach to understand adaptability, continuity, and change in the context of challenging structures and struggles, such as privatization, poverty, unemployment, inequality, and marginalization. The premises of open market and neoliberalism imposed from above by the state affected the development of the state-society relations and marginalization. They resulted in a change in the subjectivities of the people and a neglectful rule by the state. As a result, the responsiblized citizen came into existence, meaning that the individualized citizen became actively responsible for his/her own wellbeing, which renders the neoliberal strategies of rule existing in different realms of our everyday life. The Zabbaleen community give a clear demonstration of the art of presence despite the marginalization, the neglectful rule, and the policies that they suffer from. Their resilience depended on three main variables: adaptation to neoliberal norms, the grassroot community development, and the unequal power relations within the community. Each of them has its own playing factors. Through these variables, the Zabbaleen community showed creativity and collective action to come up with new spaces and opportunities from what is already available to them, protecting themselves, meeting their needs, and struggling for a net result of politics of redress by their individual acts.